The Urgency of Legal Development In The Era of Globalization Based on The Values of Pancasila as National Ideology - Suwardi, Suwardi (CV. Publikasi Indonesia, 2023)
Legal development in the era of globalization based on the values of Pancasila as the nation's ideology is an urgent need. Globalization has presented complex challenges in various aspects of people's lives, including in the legal domain. This study aims to examine the urgency of legal development rooted in the values of Pancasila as the ideological foundation of the Indonesian nation. This research highlights the importance of maintaining the sustainability of Pancasila values in the context of globalization, where various foreign influences can threaten the integrity of national cultures and values. The problem to be discussed in this study is how theurgency oflegal development in the era of globalization based on Pancasila values as thenation's ideology. The research methodused is a normative research method with a statute approach and analyzed using content analysis